Development of modified titania nano photocatalysts to synergise visible light utilisation for enhanced photocatalysis / Leong Kah Hon - Leong, Kah Hon (2015)
The present thesis focused on the development of modified titania nano photocatalysts to synergise enhanced visible light photocatalysis that niched for the destruction of lethal aquatic pollutants. In preliminary phase template TiO2 was successfully synthesised through a facile non-hydrolitic sol-gel technique. The materials chemistry revealed the pristine anatase phase and crystallinity of TiO2. It also demonstrated the influence of crystallinity over photocatalysis efficiency. This was well reflected in photocatalysis evaluation studies under solar irradiation where good crystallinity shown a better photodegradation performance over the non-crystalline. The inherent photocatalytic characteristics of the synthesised TiO2 was modified and enhanced by incorporating the noble characteristic derived from palladium (Pd) and silver (Ag). This was achieved through a smart, ease and sustainable method. The adopted novel method explicitly revealed the capability of sunlight for anchoring the noble metal onto TiO2 with controlled particle size of Pd NPs (17-29 nm) and laid pathway for the effective absorbance of visible matter triggered by the synergetic effect of LSPR. Similarly, a collective oscillation of conduction electrons that were induced by the deposited Ag NPs onto the TiO2, drastically enhanced the light absorption of the composite. Moreover these noble NPs also contributed for extending the lifetime of electrons and holes pairs. The study also expressed the variation of these noble metal loading and its influence on the photocatalysis irradiated under artificial visible light. The photocatalysis evaluation studies were performed with lethal and endocrine disrupting compounds (EDCs) of different classification. This includes Amoxicillin for antibiotics and 2, 4-dichlorophenol (2, 4-DCP) for pesticides. Both the composites exhibited an excellent photocatalysis under the artificial visible light with an efficiency of 97.5 % and 63.5 % for removing AMX by Pd/TiO2 and Ag/TiO2 respectively. In addition the Ag composite also demonstrated similar photocatalysis efficiency for 2, 4-DCP. However the optimal metal loading for an ideal photocatalysis was found to be 0.5wt% for Pd/TiO2 and 3.0wt% for Ag/TiO2. Furthermore in order to enhance the characteristics of the TiO2 the conducting carbon materials were considered along with the noble metal. The reduced graphene oxide (RGO) a category of conducting carbon was considered for the ternary composite along with Ag. The ternary shown an increased visible light absorption characteristics over the binary composite. This was acknowledged to the intrinsic nature contributed by the RGO. The study also clarified the promotion of electron mobility and prolongation of the lifetime of the charge carriers. This was well correlated with the photocatalysis evaluation achieved through both good and poor photosensitizing pollutants namely Methylene Blue (MB), Reactive Blue 19 (RB19) and Bisphenol A (BPA). The objective was further extended with exploring the prospective Graphitic Carbon Nitride (g-C3N4) a semiconductor carbon compound as a visible light enhancer. The wrapping of g-C3N4 onto the surface of TiO2 drastically increased the absorption intensity in-between 390-460 nm and shifted the absorption edge to 460 nm. Subsequently, it well correlated with the photocatalysis efficiency whereby (g-C3N4)-Ag/TiO2 showed the highest photodegradation rate under artificial visible light. Hence, the present studies progressively presented the caliber of the synergisation of conventional photocatalyst to upbeat the limitations and developed a new category of composite photocatalyst. The synthesised photocatalysts well proved their candidature as an active visible light photocatalyst and laid a sustainable pathway for environmental cleanup as demanded by the planet.